Increased right ventricular septomarginal trabeculation mass is a novel marker for pulmonary hypertension: comparison with ventricular mass index and right ventricular mass - Vogel-Claussen, Jens; Shehata, Monda L.; Loßnitzer, Dirk; Skrok, Jan; Singh, Sukhminder; Boyce, Danielle; Lechtzin, Noah; Girgis, Reda E.; Mathai, Stephen C.; Lima, Joao A.; Bluemke, David A.; Hassoun, Paul M. (Investigative radiology, 2011)
Objective: - To prospectively evaluate the cardiac magnetic resonance (MR) imaging-derived measurement of right ventricular (RV) septomarginal trabeculation (SMT) mass as a noninvasive marker for pulmonary hypertension (PH), compared with the ventricular mass index (VMI = RV mass/left ventricular mass) and RV mass. - Materials and Methods: - A total of 49 patients (60 ± 12 years; 35 female) with suspected PH underwent cardiac MR and right heart catheterization on the same day. Eighteen normal volunteers were also included. The performance of SMT mass, VMI and RV mass measurement, with regard to PH detection, was analyzed using receiver operating characteristic curves. Logistic regression analysis was used to assess the association between SMT mass, RV mass, VMI, and PH. - Results: - The area under the receiver operating characteristic curve for SMT mass/body surface area (BSA), VMI, and RV mass/BSA in diagnosing the presence or absence of PH was 0.88, 0.87, and 0.73 respectively. In multivariable models, both SMT mass/BSA (P = 0.005, odds ratio: 8.6) and VMI (P = 0. 012, odds ratio: 1.1) were found to be significant, independent predictors of PH. - Conclusion: - Compared with right heart catheterization measurement, SMT mass and VMI are reproducible and noninvasive MR imaging markers for the diagnosis of PH.